Are the results of wellbeing surveys utilized in organizational development or are they ignored? Finnish Public Sector Study - Alila, Annemari (fi=Turun yliopisto|en=University of Turku|, 2018)
Psychosocial risks such as job strain, discrimination and organizational injustice are modern workplace hazards that have negative influence on employees’ health and wellbeing. Their prevention is important and has been highlighted by national legislations, the EU and other major organizations. Despite the current weak evidence supporting organizational interventions, are organizational interventions considered to be a cost-effective way to tackle psychosocial risks in large working populations. This study investigated, whether the results of wellbeing surveys are used in organizational development. No previous studies have been made on the topic. The data were derived from the ongoing Finnish Public Study (FPS). Aggregated work unit level data of the 2016 psychosocial employee wellbeing survey results was used. The survey included 65 089 respondents, who worked for 10 775 work units in 11 Finnish towns. The data were grouped into 62 variables and the results were demonstrated in the FPS feedback portal (portal). Also, signal colors were used in the results displayed in the portal to notify the work units belonging to the 10th percentile of the highest and lowest performing work units of their performance level. The work units were instructed to record one to three development initiatives i.e. targets of development into the portal based on their survey results, which indicated performance level of the work units This study had three research aims. The first (Q1) was investigate whether the work units that have and have not set development initiatives differ from each other based on psychosocial wellbeing survey variables such as job strain, job demands, discrimination and support from superiors and background variables of for example mean age and the proportion of women. The second and third aims were to ascertain whether the set development initiatives were associated with the levels of the survey variables (Q2) and the signal colors used to indicate the best and worst performing work units (Q3). Based on the results of this study, the set development initiatives were largely associated with the level of the variables. Also, the colors indicating performance level seemed to steer the development initiatives. Poorer scores and signal colors indicating poor performance were associated with greater probability of choosing the variable as a target for development initiative. Thus, the work units that set development initiatives did use the psychosocial employee wellbeing survey in organizational development. Furthermore, the results of this study indicate that development initiatives may be used as a part of strategic management. Also, differences between work units that did and did not set development initiatives were observed.